Rapid integer ambiguity resolution in GPS precise point positioning - Geng, Jianghui (2011)
GPS precise point positioning (PPP) has been used in many scientific and commercial applications due to its high computational efficiency, no need for any synchronous measurements from a nearby reference receiver and homogeneous positioning quality on a global scale. However, these merits are devalued significantly by unresolved ambiguities and slow convergences of PPP. Therefore, this thesis aims at improving PPP’s performance by resolving ambiguities for a single receiver and accelerating the convergences to ambiguity-fixed solutions in order to achieve a centimeter-level positioning accuracy with only a few seconds of measurements.